Liu Xiaobo, Charter 08, and the challenges of political reform in China - Béja, Jean-Philippe; Fu, Hualing; Pils, Eva (Hong Kong University Press, 2012)
On the sixtieth anniversary of the Universal Declaration of Human Rights, Charter 08, a manifesto asking for the transformation of the People's Republic into a Federal Republic based on separation of powers, a multi-party system, and the rule of law, was sent to the Chairman of the People's Republic of China (PRC). It was signed by 303 persons from all walks of life: intellectuals and ordinary people, communist party members and dissidents. Two days before it was made public, one of its initiators, Liu Xiaobo, was taken away from his home by the police. After more than twelve months in detention, he was sentenced to eleven years in jail for "incitement to subversion of state power." Two years later, Liu was awarded the Nobel Peace Prize, a decision the Chinese leaders considered a display of hostility by Western powers. But why had they reacted with such severity to a nonviolent petition signed by such a small proportion of the population?